Pelatihan Penggunaan Octave pada Pembelajaran Matematika untuk Guru-Guru SMA di Kabupaten Sukabumi Provinsi Jawa Barat - Lukita Ambarwati; Devi Eka Wardani Meganingtyas; Leny Dhianti Haeruman; Jason Christiawan Widiaputera; Ananda Fitri Rahmawati (Faculty of Engineering, Universitas Semarang, 2025)
An important aspect that needs attention to support success in the learning process is the teacher's competency. One of the key competencies required by teachers is mastery of technology, which supports the development of TPACK (Technological Pedagogical Content Knowledge)-based learning. Additionally, mastery of technology can help develop learning media and serve as a learning aid. One of the software that can be used as an option for learning media is Octave. Octave is open-source software, allowing teachers to access it for free. It can be used as a medium/teaching tool to explain various mathematical concepts, such as functions, function limits, derivatives, integrals, and more. This training was attended by high school teachers and took place at Al Bayan Superior High School, Sukabumi Regency. During the training, participants were taught how to use Octave in mathematics instruction to enhance teacher competency. The results of the training show that the use of Octave can support learning in schools by boosting teacher competency and inspiring teachers to become more professional. This, in turn, leads to improved learning quality in schools, which ultimately enhances the overall quality of education.